1998
DOI: 10.1021/bi973162p
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inactivation of Parvulin-Like Peptidyl-Prolyl cis/trans Isomerases by Juglone

Abstract: In contrast to FK506 binding proteins and cyclophilins, the parvulin family of peptidyl-prolyl cis/trans isomerases (PPIases; E.C. 5.2.1.8) cannot be inhibited by either FK506 or cyclosporin A. We have found that juglone, 5-hydroxy-1,4-naphthoquinone, irreversibly inhibits the enzymatic activity of several parvulins, like the E. coli parvulin, the yeast Ess1/Ptf1, and human Pin1, in a specific manner, thus allowing selective inactivation of these enzymes in the presence of other PPIases. The mode of action was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
282
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(297 citation statements)
references
References 33 publications
8
282
0
7
Order By: Relevance
“…Neither CsA nor FK506 inhibited this activity (Table II), indicating that the PrsA preparations were not contaminated with cyclophilins or FKBP-type PPIases. They were also free of the E. coli parvulin, since juglone did not affect the activity (31). These results suggest that PrsA is a PPIase.…”
Section: The N-terminal C-terminal and Parvulin-like Regions Arementioning
confidence: 74%
See 1 more Smart Citation
“…Neither CsA nor FK506 inhibited this activity (Table II), indicating that the PrsA preparations were not contaminated with cyclophilins or FKBP-type PPIases. They were also free of the E. coli parvulin, since juglone did not affect the activity (31). These results suggest that PrsA is a PPIase.…”
Section: The N-terminal C-terminal and Parvulin-like Regions Arementioning
confidence: 74%
“…Cyclosporin A (CsA, Sigma-Aldrich) and FK506 (Calbiochem) were used at 5 M concentrations to inhibit PPIase activities of putative contaminating cyclophilins and FKBP-type PPIases in the PrsA preparations, respectively. Juglone (Sigma-Aldrich), which is an inhibitor of numerous parvulins, was used at 7 M concentrations as described (31). Cyclophilin, which was used as a positive control, was from calf thymus and was purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Different research groups are currently developing Pin1 small-molecule inhibitors, whose efficacy in anticancer therapy should be tested in vivo. [32][33][34] Furthermore, we have found that the other two members of the pocket protein family, namely p130/pRb2 and p107, are substrates of Pin1. As in T98G cells the Pin1 and pRb interaction plays a major role in the G1/S cell cycle control, it would be interesting to analyze Pin1, pRb2/p130, and p107 in other cancer cells or other physiological processes.…”
Section: Discussionmentioning
confidence: 89%
“…The compound covalently inactivates a cysteine residue in the active site of Pin1 isomerase (39). Intraperitoneal juglone injection was done every other day after a booster injection of CII and continued for 9 days (total four times).…”
Section: Juglone Inhibits Ra Progress In Cii-inducible Dba/1j Mice Anmentioning
confidence: 99%